ANALYSIS OF FACTORS AFFECTING THE DEVELOPMENT OF MICRO, SMALL AND MEDIUM ENTERPRISES (MSMEs) IN RURAL AREAS - Dede Husni Mubarok; Maulida Hikmatul Husna; Dudung Rahman Wahid (Syari'ah Economics, 2020)
This study aims to elaborate on the factors that influence the development of micro, small and medium enterprises (MSMEs) in rural areas. This study uses a quantitative approach, because the data obtained is realized in the form of numbers and analyzed based on statistics. Based on the research method used, this research is an associative-causal research. Data collection techniques using a questionnaire with test requirements include validity test and instrument reliability test and normality test. Hypothesis test using Pearson Product Moment correlation, multiple correlation, simple regression, and multiple regression. The results of the study show (1) there is a significant influence of marketing factors on the development of MSMEs. (2) Working capital has a significant effect on the development of MSMEs. (3) The variables of marketing and capital have a significant effect on the development of MSMEs.